2016
DOI: 10.1680/coma.15.00011
|View full text |Cite
|
Sign up to set email alerts
|

Waste glass aggregate for cementitious and polymer concrete

Abstract: Glass waste is produced in considerable amounts annually. Due to the disadvantageous nature of its recycling process, its reuse gains importance. Given the high reactivity level of glass-incorporating mixtures, the reuse of waste glass as aggregate in polymer concrete was investigated. Polymer concrete mixtures, including unsaturated polyester resin, hardener and accelerator, waste glass aggregate (up to 8 mm) and glass fabrics, were prepared for the investigation of mechanical properties. The composite specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In geopolymer concretes, the addition of WG powder causes a reduction in thermal conductivity for the minimal interconnections in the internal pores, thereby preventing the temperature flow inside the composite [ 45 ]. The coefficient of thermal conductivity of WG concrete was slightly higher than the PC in the observation of Andiç-Çakır et al [ 23 ], in which the conductivity increased with an increase in the particle size of WG aggregates. This finding was attributed to the densely packed matrix and low air voids within the hardened composite.…”
Section: The Durability Of Concrete With Wgmentioning
confidence: 88%
See 3 more Smart Citations
“…In geopolymer concretes, the addition of WG powder causes a reduction in thermal conductivity for the minimal interconnections in the internal pores, thereby preventing the temperature flow inside the composite [ 45 ]. The coefficient of thermal conductivity of WG concrete was slightly higher than the PC in the observation of Andiç-Çakır et al [ 23 ], in which the conductivity increased with an increase in the particle size of WG aggregates. This finding was attributed to the densely packed matrix and low air voids within the hardened composite.…”
Section: The Durability Of Concrete With Wgmentioning
confidence: 88%
“…One of the major challenges of WG concrete is the presence of high silica, and alkali content in glass and cement causes the ASR, which could cause expansive gel formation [ 22 , 23 , 92 ]. The ASR expansion is accelerated with the presence of Na and K ions [ 92 ].…”
Section: Challenges In Wg Concrete and Remediesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Andiç-Çakir et al (2016) are concerned about how to utilise some 12-13 million tonnes of glass waste material generated annually worldwide, especially as it might not be possible to consume it in concrete or other cementitious materials, owing to possible resultant alkali-silica reactivity (ASR). They propose using some of the glass as aggregate within polymer concrete, when ASR is not an issue, and their tests indicated that this would be feasible, when the concrete could also employ glass fabric reinforcement.…”
mentioning
confidence: 99%